Physical Activity and Quality of Life in Head and Neck Cancer Survivors: A Literature Review - Sammut, L.; Ward, M.; Patel, N. (International Journal of Sports Medicine, 2014)
The head and neck region is highly complex in terms of its anatomy and physiology. Head and neck cancer (HNC) and the treatment thereof can significantly affect both the structure and function of this area, especially in terms of swallowing, breathing and speaking. This may lead to a significant reduction in quality of life (QOL), and present challenges to both patients and their caregivers. There is increasing evidence that physical activity (PA) after a diagnosis of cancer is associated with improved overall mortality. This is well established in colon, prostate, ovarian and breast cancer. 2 recent metanalyses have determined that exercise interventions following cancer diagnosis are associated with a 41% reduction in risk of all-cause mortality, and an improvement in QOL. PA has also been found to be valuable in counteracting symptoms that reduce QOL, including depression, fatigue, worry and anxiety. Given that HNC patients face their own unique set of challenges, and may have different needs than other cancer patients, we have reviewed the available literature on the interactions between exercise and QOL in HNC patients.
Keywords: cancer; physical activity; quality of life; head and neck